2015
DOI: 10.1007/s10899-015-9549-7
|View full text |Cite
|
Sign up to set email alerts
|

Cue-Reactive Altered State of Consciousness Mediates the Relationship Between Problem-Gambling Severity and Cue-Reactive Urge in Poker-Machine Gamblers

Abstract: In order to enhance our understanding of the nature of poker-machine problem-gambling, a community sample of 37 poker-machine gamblers (M age = 32 years, M PGSI = 5; PGSI = Problem Gambling Severity Index) were assessed for urge to gamble (responses on a visual analogue scale) and altered state of consciousness (assessed by the Altered State of Awareness dimension of the Phenomenology of Consciousness Inventory) at baseline, after a neutral cue, and after a gambling cue. It was found that (a) problem-gambling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…The current findings can be interpreted within a cue-reactivity framework. Tricker et al (2016) found that increased cue-reactivity is mediated by an altered state of consciousness, which they suggest not only elicits urges, but also elicits cognitive biases that are normally active under gambling ( Toneatto, 2002 ). Such an interpretation might explain the findings from previous studies suggesting that GD are more influenced by promotional marketing compared to non-problem gamblers, which is explained by those with GD viewing the offers as more attractive due to cue-activated cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…The current findings can be interpreted within a cue-reactivity framework. Tricker et al (2016) found that increased cue-reactivity is mediated by an altered state of consciousness, which they suggest not only elicits urges, but also elicits cognitive biases that are normally active under gambling ( Toneatto, 2002 ). Such an interpretation might explain the findings from previous studies suggesting that GD are more influenced by promotional marketing compared to non-problem gamblers, which is explained by those with GD viewing the offers as more attractive due to cue-activated cognitive biases.…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, the nature of the cue-reactive methodology dictates that the phenomenological variables of interest (imagery and volitional control) were evaluated based on participant retrospective report regarding their experience during cue-exposure [ 51 ]. As such, it would not be expected that the affect labelling task, which took place immediately following the cue exposure, would impact upon these variables.…”
Section: Resultsmentioning
confidence: 99%
“…To measure subjective anxiety in response to cues, participants rated their level of current anxiety on a scale of 0 (no anxiety) to 100 (extreme anxiety). Visual analogue scales have been widely used in emotional regulation and cue-reactivity studies and are considered a sensitive measure [ 18 , 51 ].…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Table 1, the authors did not define the construct univocally. Although most used the term dissociation, others referred to it as the flow (Dixon et al, 2019;Murch et al, 2017), ASA (McKeith et al, 2017), and altered state of consciousness (Tricker et al, 2016), with few studies contemporary investigating more than one of these variables. Depending on the type of construct considered, there is a difference in the choice of tests used.…”
Section: Systematic Review Of Studiesmentioning
confidence: 99%
“…The PCI assesses 12 dimensions of phenomenological experience (e.g., Time Sense, Imagery, Volitional Control, Arousal, and ASA). The ASA dimension consists of three pairs of questions rated on a seven-point dipole scale (0-6), enquiring about the occurrence of unusual states of consciousness (Tricker et al, 2016).…”
Section: Systematic Review Of Studiesmentioning
confidence: 99%